2017
DOI: 10.1016/j.tiv.2017.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Development of a common carp (Cyprinus carpio) pregnane X receptor (cPXR) transactivation reporter assay and its activation by azole fungicides and pharmaceutical chemicals

Abstract: In mammals, the pregnane X receptor (PXR) is a transcription factor with a key role in regulating expression of several genes involved in drug biotransformation. PXR is present in fish and some genes known to be under its control can be up-regulated by mammalian PXR ligands. Despite this, direct involvement of PXR in drug biotransformation in fish has yet to be established. Here, the full length PXR sequence was cloned from carp (Cyprinus carpio) and used in a luciferase reporter assay to elucidate its role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 53 publications
4
14
0
Order By: Relevance
“…Crystallization of zfPXR in complex with steroids and mutagenesis of the main amino acids in contact with the steroids in the zfPXR pocket would enable to confirm this selectivity. We also showed that the synthetic glucocorticoid dexamethasone and the pregnane pregnenolone 16a-carbonitrile, which are mouse PXR agonists, do not modulate zfPXR in accordance with what was previously reported with carp and zebrafish receptors (6,8,27).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Crystallization of zfPXR in complex with steroids and mutagenesis of the main amino acids in contact with the steroids in the zfPXR pocket would enable to confirm this selectivity. We also showed that the synthetic glucocorticoid dexamethasone and the pregnane pregnenolone 16a-carbonitrile, which are mouse PXR agonists, do not modulate zfPXR in accordance with what was previously reported with carp and zebrafish receptors (6,8,27).…”
Section: Discussionsupporting
confidence: 91%
“…The PGL4.24-6xPXRE reporter plasmid ( 6 ) is a kind gift from Anke Lange and Charles Tyler. The PXRE6-TATA-luciferase-hygromycin was constructed by adding the hygromycin resistance in this plasmid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-based assays allow the study of the MoA of ligand-activated transcription factors (nuclear receptors) including PXR, PPARs, ERs and AhR (Raucy and Lasker, 2013;Puy-Azurmendi et al, 2014), which recognize a wide range of structurally-unrelated ligands acting as osteotoxicants. Recently, a transactivation reporter assay has been developed for the common carp (Cyprinus carpio) PXR and compared with the human isoform under the exposure to various fungicides and pharmaceuticals (Lange et al, 2017), further confirming the differential hability of tested compounds to activate fish and human PXR isoforms previously reported (Ekins et al, 2008).…”
Section: Fish Systems For Osteotoxicitysupporting
confidence: 62%
“…cytochromes) in humans and is activated by a wide range of xenobiotics (e.g antibiotics) as well as endobiotics [63]. Activation of PXR has previously been observed by other azole fungicides such as miconazole and propiconazole [64] (see Fig. 7a, b).…”
Section: Knowtox-case Studymentioning
confidence: 69%